Phenological traits foster persistence of mutualistic networks by promoting facilitation. (4th July 2021) - Duchenne, François; Fontaine, Colin; Teulière, Elsa; Thébault, Elisa
Abstract: Morphological and phenological traits are key determinants of the structure of mutualistic networks. Both traits create forbidden links, but phenological traits can also decouple interaction in time. While such difference likely affects the indirect effects among species and consequently network persistence, it remains overlooked. Here, using a dynamic model, we show that networks structured by phenology favour facilitation over competition within guilds of pollinators and plants, thereby increasing network persistence, while the contrary holds for networks structured by morphology. We further show that such buffering of competition by phenological traits mostly beneficiate to specialists, the most vulnerable species otherwise, which propagate the most positive effects within guilds and promote nestedness. Our results indicate that beyond trophic mismatch, phenological shifts such as those induced by climate change are likely to affect indirect effects within mutualistic assemblages, with consequences for biodiversity. Abstract : By developing a theoretical model including phenological and morphological structures in interactions, we show that mutualistic communities structured by phenological traits exhibit higher viability, species coexistence and nestedness than communities structured by morphological traits. We find that these contrasting effects on viability and coexistence arise from a shift in the balance between positive and negative indirect interactions among species, with phenological traits favouring within guild facilitation over competition contrary to morphological traits.